Исследование влияния крупности легирующего элемента шихты на свойства диффузионного слоя - Товажнянский, Леонид Леонидович; Быков, Антон Александрович (НТУ "ХПИ", 2006)
The statistical model for evaluation of the optimum coarseness of main mixture component for DCSA process has been presented.
Keywords: шихта; хромирование